Response of Health Personnel on Medical Waste At Upazilla Health Complexes under Dhaka Division in Bangladesh (Bangladesh Journal of Dental Research & Education, 2013)
This cross sectional study was conducted among health personnel working in 7 Upazilla Health Complexes and support staff without medical background but concerned with waste management. A total of six respondents (doctors, nurses and & support staff, 2 each) from each Upazilla with average bed occupancy >10/day and where there are > 10 health personnel in position were selected. The objective of this study was to assess the health personnel whether they can identify the waste in the Health Complexes. The present study interviewed 42 respondents of which one third each were doctors, nurses, and support staff. In response to a question on type of waste generated at the Health Complex, 19.0% said infectious waste, 16.7% said pharmaceutical waste, 21.4% said pathological & anatomical waste, 23.8% said sharp waste and 19.0% said pressurised container. From response about different medical wastes, it shows that respondents know better about hazards of sharp waste and liquid waste. However, about other types of wastes like infectious waste, pathological waste, pharmacological waste, chemical waste, heavy metal waste, pressurized container and highly infectious waste the level of knowledge is rather poor or had no knowledge. Further study should be conducted on the issue with larger sample size and greater logistic support to reveal more generalized picture of country situation.DOI: http://dx.doi.org/10.3329/bjdre.v3i1.16587 Bangladesh Journal of Dental Research & Education Vol.3(1) 2013: 1-5